ANALYSIS OF ENERGY CRITERIA FOR WAVELET TRANSFORMS IN COMPOSITE STRUCTURES - Писаренко, Олександр (SWorldJournal, 2024)
This work is devoted to the analysis of the effectiveness of wavelet transformations for the localization of deformations in composite materials obtained by the acoustic emission method. A detailed comparison of several discrete wavelet transformations w